Representing and Promoting Family Literacy on the World Wide Web: A Critical Analysis - Anderson, Jim; Streelasky, Jodi; Anderson, Terri (Alberta Journal of Educational Research, 2007)
The purpose of this study was to examine critically how family literacy is promoted and represented through the images and written texts on Web sites developed by providers of family literacy programs. Naturalistic research over the last 20 years or so demonstrates that the family is a rich site for supporting children’s literacy development across socioeconomic and cultural contexts. This research suggests that families engage children in a wide array of literacy activities in their daily experience. Furthermore, many significant others in addition to parents play important roles in children’s literacy development. In this study we examined a representative sample of family literacy Web sites from across Canada. Findings suggest that literacy tends to be narrowly defined; responsibility for children’s literacy is usually ascribed to mothers; and troubling assumptions about families as being deficient still persist.